On Local and Nonlocal Robin Boundary Value Problem with Critical Nonlinearity (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, using the Mountain Pass Theorem, we present results on compactness and the existence of solutions for a class of local and nonlocal $p$-Laplacian equations involving Robin boundary conditions, with criticalnonlinearity and a small perturbation.